Representasi Masalah Sosial Remaja Dalam Novel Areksa Karya Ita Kurniawati: Teori Sosiologi Sastra Ian Watt - Joy Grace Bestari Simamora; Nina Queena Hadi Putri; Alfian Rokhmansyah; Nia Novita Putri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the representation of adolescent social problems in the novel Areksa by Ita Kurniawati. The novel portrays various adolescent issues, including family conflict, interfaith romantic relationships, and the influence of peer group subculture in the process of identity formation. This study aims to describe the forms of adolescent social problems presented in the novel and to analyze their relationship with social realities through the perspective of the sociology of literature proposed by Ian Watt. This research employs a qualitative approach using content analysis. The data consist of quotations of dialogues and narrative passages in the novel that reflect adolescent social problems. Data were collected through a literature study using reading and note-taking techniques and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal three major forms of adolescent social problems: family dysfunction that leads to communication breakdown within the domestic sphere, the dynamics of interfaith romantic relationships influenced by social and religious norms, and peer group subcultures that function as alternative spaces for adolescent identity formation. These findings indicate that Areksa functions not only as a work of entertainment but also as a reflection of the social realities experienced by contemporary adolescents shaped by family dynamics, social norms, and peer group subcultures.